HUBUNGAN DUKUNGAN TEMAN SEBAYA DAN KEPERCAYAAN DIRI SISWA PADA SENAM LANTAI SD - Bisono Yudanto, Zulfikar; Darmawan, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between peer support and students' self-confidence in elementary school floor gymnastics lessons. The research used a quantitative approach with a correlational design. The population was 150 students in grades 5 and 6. The sampling technique used total sampling. The instrument was a Likert scale questionnaire measuring peer support (15 items) and self-confidence (12 items). Data analysis techniques include descriptive analysis with the categorization of Ideal Mean (MI) and Ideal Standard Deviation (SDI), prerequisite tests (normality and linearity), and hypothesis testing using Pearson Product Moment correlation. The results showed that peer support level was in the high category for 75% of students and moderate for 25%. Self-confidence level was in the high category for 69% and moderate for 31%. There was a significant and positive relationship between peer support and student self-confidence, with a correlation coefficient of 0.557 and significance value of 0.000 (p < 0.05). The coefficient of determination (R²) value of 0.311 indicates that peer support contributes 31.1% to students' self-confidence, while the remaining 68.9% is influenced by other factors not studied. The conclusion is that higher peer support leads to higher student self-confidence in floor gymnastics learning.